Lingua receptiva in Europe: the map and the territory - Steciąg, Magdalena (Przegląd Wschodnioeuropejski, 2020)
As a result of complex and closely-related social, political, economic and technological processes, significant changes are now occurring in the European language situation. While these processes foster participation in the transnational communication community, they also reinforce the linguistic identity, based on their distinction. In view of these contradictory but non-exclusive trends, one should consider the multilingual systems that would better reflect the dynamics of real changes. For this purpose, the concept of lingua receptiva will be presented. Geographical and cultural perspectives are taken into account in this paper. Emphasis is on the space of discursive interculturalism, in which contacts in more or less fixed language constellations constantly take place. Its allocation on the political map of the European continent is not performative, but based on the literature. However, it does illustrate the challenges for the future of European receptive multilingualism.